Oligodeoxinucleotídeos CpGs protegem Jundiás (Rhamdia quelen) do desafio por Aeromonas hydrophila - Canova, Raissa (2016)
In this study we evaluated the effect of different CpGs ODN on their ability to modulate the innate immune system of silver catfish (Rhamdia quelen). The CpGs ODNs 1668, 2102, 2133 and 2143 were selected based on their characteristics and because their immunological effect has already been reported in other vertebrate species, including fish. To evaluate the protecting effect of CpGs ODNs, groups of fish were intraperitoneally inoculated (i.p.) with each CpGs ODNs and 24h after they were i.p. inoculated with Aeromonas hydrophila (2×108 UFC/fish). The protective effect was evaluated by recovering the bacteria from blood and fish mortality. In the first experiment, silver catfish were divided in 5 groups (40 fish/group); each fish was inoculated with 0.1ml of CpG ODN (0.5g/fish) and fish from the control group were inoculated with 0.1 ml of PBS. Then, 24h after CpGs ODNs or PBS inoculation, all fish were inoculated with A. hydrophila (2×108 CFU/fish; 0,1 ml). And, 24 h post-challenge with A. hydrophila, blood samples were collected from at least 10 fish per group aiming to detect bacteremia. The remaining fish (n=30) were monitored and the number of death fish was daily annotated for up to seven days. In thisexperiment, fish inoculated with CpG ODN 1668, 2102 and 2133 had significantly lower (p<0.05) bacteremia than fish from the CpG ODN 2143 or control group. In the CpG ODN 1668 group, the percentile of fish with bacteremia was only 50% whereas in the CpG ODN 2102 group, the percentile of fish with bacteremia was 92%. In the other groups the percentile of fish with bacteremia was 100%. In addition, in the group inoculated with CpG ODN 1668, the survival (95%) and significantly higher (p<0.05) when compared to the other groups. Thus, the remaining experiments were carried out using CpG ODN 1668. And, to evaluate the effect of the dose of CpG ODN 1668, 4 groups of fish (10 fish/group) were inoculated with 0.004μg, 0.02μg, 0.1μg or 0.5μg/fish, respectively. Control group received PBS; bacteria challenge and recovery from blood was performed as described above. Here, fish inoculated with 0.1g and 0.5g of CpG ODN had significantly lower (p<0.05) bacteremia than fish from the control group. In this 2 groups, the percentile of fish with bacteremia was 45% compared to 88,7% of fish with bacteremia in the control group. To evaluate the effect of time of CpG ODN administration on the level of bacteremia, CpG ODN 1668 (0.5 g/fish) was inoculated at 7 days, 96, 48 or 24h prior to A. hydrophila challenge (2 × 108CFU/fish). The control group was inoculated with PBS prior to challenge and bacteria recovery from blood was carried out as indicated above. In this experiment, fish inoculated with CpG ODN 1668 at 96h prior to challenge had significantly (p<0.05) lower bacteremia compared to the other groups. In addition, in the fish inoculated with CpG ODN at 96h prior to challenge, the percentile of fish with bacteremia was 80% whereas in the remaining groups the percentile of fish with bacteremia was 100%. Thus, with these studies we concluded that i.p. inoculation of CpGs ODNs stimulates protection against challenge with A. hydrophila in silver catfish, reducing bacteremia and increasing fish survival rate. Our data suggest that the protective effect of CpG ODN depends on the nucleotide sequence, dose and time of administration prior to fish challenge.